Indoor sensing technology based on channel state information - Zhefu WU; Han WANG; Cheng CHEN; Zhongyou WANG; Wei HUANG (Dianxin kexue)
The wide spread wireless network has brought about tremendous development of mobile internet business services and has become one of the infrastructures of modern society.The basic principles and implementation methods of wireless sensing technology were expounded from the perspective of wireless channel state analysis.The technological innovation in the field of wireless sensing in recent years was discussed,especially channel state information based human body posture detecting and environmental monitoring.Finally,the future development trend of sensing technology based on wireless communication network was analyzed in order to provide reference for related research.